Joint-Specific Contributions to Vertical and Horizontal Center-of-Mass Velocity During a Sit-to-Stand Task Depend on Age. - Ahn, Nayun; Lewis, Cara L.; Kipp, Kristof (Journal of Applied Biomechanics, 2025)
This study aimed to compare the contributions of lower limb net joint moments (NJM) to the control of vertical and horizontal center-of-mass (COM) velocities during the momentum transfer and extension phases of the sit-to-stand (STS) task between healthy young and older adults. Eighteen young and 16 older adults performed STS 5 times at their self-selected speed. Kinematic and kinetic data were collected and used to calculate ankle, knee, and hip NJM. Induced acceleration analysis was used to identify the joint-specific functional roles and NJM contributions to the vertical and horizontal COM velocities during STS. The NJM at all 3 joints contributed to the upward velocity of the COM. The NJM contributions to the vertical COM velocity were greater in older adults compared to young adults during the momentum transfer phase, suggesting older adults may use a different COM control strategy in this direction. For horizontal velocity, knee NJM slowed forward COM motion, while the hip and ankle NJM sped up forward motion. The NJM contributions to the horizontal COM velocity were not influenced by age, which may suggest that healthy older adults retain the ability to control and regulate horizontal COM velocity to a greater extent than vertical COM velocity.